2019
DOI: 10.1055/a-1022-1554
|View full text |Cite
|
Sign up to set email alerts
|

3-Iodothyronamine Induces Diverse Signaling Effects at Different Aminergic and Non-Aminergic G-Protein Coupled Receptors

Abstract: The thyroid hormone metabolite 3-iodothyronamine (3-T1AM) exerts diverse physiological reactions such as a decrease of body temperature, and negative inotropic and chronotropic effects. This observed pleomorphic effect in physiology can be barely explained by interaction with only one target protein such as the trace-amine receptor 1 (TAAR1), a class A G-protein coupled receptor (GPCR). Moreover, Taar1 knock-out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…In this respect, no evidence is available yet. The affinity of T1AM for G protein-coupled receptors was reported in the µM range, while the concentration of T1AM here used was in the nM range [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, no evidence is available yet. The affinity of T1AM for G protein-coupled receptors was reported in the µM range, while the concentration of T1AM here used was in the nM range [10].…”
Section: Discussionmentioning
confidence: 99%
“…T1AM systemically administered concentrates in several T3 target organs including the liver and the white adipose tissue, where it activates lipolysis with a concomitant inhibition of adipogenesis [9]. Among T1AM targets are membrane-bound [10], but also intracellular proteins, among which is mitochondrial F(0) F(1)-ATP synthase [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-Iodothyronamine (3-T1AM) is a metabolite product of the thyroid hormones (TH) which exerts an opposite physiological function of classical TH such as a decrease of body temperature and metabolic rate in rodents [1]. Several studies have shown that 3-T1AM is presumed to act on various organs and different receptors rapidly [2]. Moreover, it has therapeutic potential for treatment of metabolic diseases [3], myocardial vascular diseases [4], and neurological diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…3-iodothyronamine (T1AM) is a metabolite product of the thyroid hormones (TH), which exert an opposite physiological function of classical TH such as a decrease of body temperature and metabolic rate in rodents [3]. Several studies have shown that T1AM is presumed to act on various organs and different receptors rapidly [4]. Moreover, it has therapeutic potential for treatment of metabolic diseases [5], myocardial vascular diseases [6], and neurological diseases [7].…”
Section: Introductionmentioning
confidence: 99%